Analisis Efisiensi Pengolahan Data Pasien Igd Dalam Implementasi Rekam Medis Elektronik (Rme) di Santosa Hospital Bandung Central - Nur Rahma Fitriani; Agri Hardian Wiharto (Jurnal Infokes, 2026)
This study aims to analyze the efficiency of patient data processing in the Emergency Department (ED) through the implementation of Electronic Medical Record (EMR) at Santosa Hospital Bandung Central. The research applied a qualitative descriptive methode with data collection techniques including observation, structured interviews, and literature review. The findings indicate that the implementation of EMR in the ED contributes significantly to improving work efficiency, accelerating access to patient information, reducing the use of paper, minimizing the accumulation of physical medical records, and facilitating coordination among health workers. In addition, EMR enables the automatic recording of triage categories and response time, both of which are essential indicators in emergency care services to ensure timely medical action. Although the system has demonstrated considerable benefits, challenges remain related to infrastructure readiness, system optimization and user adaptation. Overall, this study concludes that EMR strongly supports more efficient, accurate, and real time patient data processing in the ED, and its application has a positive impact on enhancing the quality of hospital services.